Drug utilisation study in medicine outpatient department at Ashwini Rural Medical College, Kumbhari, Solapur, India - Bhalerao, Pramod P.; Waghmare, Chandrakant S. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Drug utilization studies are used to analyze different aspects of the use of drugs and to implement methods of improving therapeutic quality. This study was conducted to study drug prescription pattern in Medicine Outpatient Department (OPD) in Ashwini Rural Medical College, Kumbhari. Methods: Six hundred prescriptions were screened & analyzed as per the study parameters at Medicine OPD of Ashwini Rural Medical College, Kumbhari. Study parameters like demographic profile of the patient like age, sex and diagnosis were recorded. Doctor details and patient details like age, sex and address were analyzed. Also, groups of drugs commonly prescribed, number of drugs per patient, drug profile and drawbacks of prescription if any were recorded and analyzed. Results: Most common group of drugs prescribed by physicians were Analgesics (21.84%), followed by Drugs for Peptic ulcer (17.92%) and Multivitamins/multimineral (14.70%). The average number of drugs prescribed per patient was 2.38. The incidence of Polypharmacy was common occurrence and some prescriptions had small drawbacks like absence of diagnosis, absence of doctor’s signature, etc. Conclusions: Authors conclude that most of the prescriptions which were analyzed at Ashwini Rural Medical College Hospital, Kumbhari, were according to the standard norms of WHO prescriptions and also most of the drugs prescribed were from the list of essential drug list. But still there is scope for improvement in prescription pattern.